The Influence of Sowing Date and Norms on the Yield of "Madad" Variety of Soybean (Texas Journal of Multidisciplinary Studies, 2022)
This article presents data on the influence of sowing period and norms of soybean variety "Madad" on the grain yield in the conditions of meadow-swamp soils of Tashkent region. According to the data, sowing of this variety early, in the period of 25.04-30.04 at the rate of 60 kg per hectare, was the highest indicator among the options, 32.3 c/ha. In this case, the additional yield from soybeans was 1.2-3.8 c/ha according to sowing dates, and 0.6-2.8 c/ha according to sowing norms.